How Important Are IEAs for Mitigation If Countries Are of the Homo Moralis Type? - Thomas Eichner; Rüdiger Pethig (Center for Economic Studies and ifo Institute (CESifo), 2024)
We analyze international environmental agreements in a two-stage game when governments have homo moralis preferences à la Alger and Weibull (2013, 2016). The countries base their decisions on the material payoff obtained on the hypothesis that all other countries act as they with predetermined probability. They are assumed to act morally w.r.t. both membership and emissions. We investigate the interaction and impact of that moral behavior on coalition formation and material payoff. The membership morality tends to increase while the emissions morality tends to decrease the coalition size, but the outcome is not smoothly determined by these opposite forces.
Keywords: C72; Q50; Q58; 330; IEA; stability; homo moralis; emissions morality; membership morality